The Colton sheriff - Fox, Addison; Mills & Boon Romantic Suspense (Sydney, New South Wales : HarperCollins Publishers, 2019)
How does a small-town sheriff track a serial killer? With the help of his fake fiancée! Running for reelection, Sheriff Trey Colton needs a bride-to-be by his side. Who better than his best friend, psychologist Aisha Allen? But as they start to play house, a serial killer terrorises their beloved town - and targets Trey. The fight for survival brings an eye-opening truth for these 'pretend' lovers - that love is precious...but death is only a heartbeat away.
Keywords: Best friends -- Fiction; Brides -- Fiction; Fiancees -- Fiction; Man-woman relationships -- Fiction; Contemporary romance; Fiction - Romance - Contemporary; Romance fiction